Interdisciplinary Research on Close Relationships: The Case for Integration.
DOI: 10.1037/13486-002
|View full text |Cite
|
Sign up to set email alerts
|

Perceived partner responsiveness as an organizing theme for the study of relationships and well-being.

Abstract: As we humans go through life, we are involved in many different goals and activities. We go to school or work; we pursue hobbies, pastimes, and other recreational interests; we socialize with friends, relatives, coworkers, and acquaintances; we care for children, aging parents, and others; and we engage in subsistence activities like preparing meals, managing finances, maintaining our living spaces and vehicles, and sleeping. Traversing all of these is the impact of relationships. Virtually all day-to-day acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

42
917
2
12

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 554 publications
(973 citation statements)
references
References 54 publications
42
917
2
12
Order By: Relevance
“…Partner responsiveness is arguably one of the most fundamental components of satisfying, committed relationships (Maisel & Gable, 2009;Reis et al, 2004). It is a pivotal marker of high quality, lasting relationships (Huston, Caughlin, Houts, Smith, & George, 2001;Karney & Bradbury, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Partner responsiveness is arguably one of the most fundamental components of satisfying, committed relationships (Maisel & Gable, 2009;Reis et al, 2004). It is a pivotal marker of high quality, lasting relationships (Huston, Caughlin, Houts, Smith, & George, 2001;Karney & Bradbury, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Desirability was manipulated in the present study by varying the degree to which targets appeared to be high in partner responsiveness. The extent to which partners have the potential for mutual responsiveness to each other's needs, and the potential for close, intimate connection is an important marker of relationship quality (Maisel & Gable, 2009;Reis, Clark, & Holmes, 2004;Spielmann, MacDonald, & Tackett, 2012). Indeed, intimacy and closeness stemming from partner responsiveness are key to creating rewarding close relationships (Laurenceau, Feldman Barrett, & Pietromonaco, 1998;Laurenceau & Kleinman, 2006).…”
Section: Chapter 6 Settling For Less: Relationship Initiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that benefits bring information about the relationship motivations of the benefactor (Ames, Flynn, & Weber, 2004), we suggest an additional critical appraisal for the emotion of gratitude that is interpersonal in nature: perceived responsiveness to the self (Reis, Clark, & Holmes, 2004 (Schwarz & Clore, 2007) in line with emotionrelevant appraisals (Lerner & Tiedens, 2006), then considering the relational implications of gratitude is essential for understanding its role in social life. As a first step, we recently found that gratitude was uniquely associated with a reappraisal of the benefactor's positive qualities and promoted relationship-enhancing motivations toward the benefactor (Algoe & Haidt, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…associated with feeling understood, valued, and cared for by another individual (Reis et al, 2004). For example, if one gives a gift certificate to a local mall or spends the same amount of money to give a CD that she knows is the recipient's favorite band, the latter better demonstrates responsiveness to one's self.…”
mentioning
confidence: 99%